Komunikasi dan Hubungan Terapeutik Perawat-Klien terhadap Kecemasan Pra Bedah Mayor - Sri Mulyani, Ira Paramastri, Much. Agus Priyanto (Berita Kedokteran Masyarakat (BKM), 2008)
Background: A patient who will  carry  a  surgical  operation  has  uncertainty  feeling,  fear,  doubt and  anxiety. Anxiety can  laid  to  psychological disruption or  functional body  disruption of  a patient  that  can affect  the surgical operation  and  anesthesia achievement. Based on  pre-research study  that has  been  carried  by  researcher  on June 2007 of 40 patients on  in-room at surgery and non-surgery  room,  it  is  found  that 52,5% at  the medium  rate of  anxiety. By  so, we need  effective way  to  decrease  anxiety  rate  of patient. This  research  is aimed  to  find  the effect  of  communication  and nurse-patient  therapeutic  relation  in decreasing  anxiety  rate  of pre-major  surgery patient.Method: Type  of  the  research  is  experimental quasi with pre-test  and post-test  group design. The samples  of the  research  consist  of  30,  that we are  given  communication  treatment and  nurse-patient  therapeutic  relation, and of 30,  that we  are not given  the  treatment. The sample  is  chosen used purposive  technique. The  technique of  collecting  data  is  questionnaire. The  data  analyzing  to  know  the difference  of  anxiety with paired  samples test, whereas  to  examine  the  effect of  communication and  nurse-patient  therapeutic  relation with  independent samples  test with  significance  rate  p=0,05.Result and Discussion: The  result of  research showed  that  there  is no  difference at  age characteristics,  sex, education,  ill  period,  and marriage  status  of  both  group  (p>0,05).  There  is  significantly  difference  anxiety (p<0,05) between  the groups.  Patients of  pre-major surgical  operation,  that were given  therapeutic  relation  and communication  treatment  by nurse,  have  anxiety  rate much more  lowly why were  not  given. Test  result  showed therapeutic  relation  and communication  treatment  is  carried between  nurse and  patient can  decrease anxiety  of pre-major  surgical operation with  p=0,00  (p<0,05).Conclusion:  Therapeutic  relation  and communication  of  nurse  and  patient  can decrease  anxiety  of  pre-major surgical  operation.Keywords: Therapeutic  relation and  communication, nurse  and  client, anxiety,  premajor  surgical  operation